Hearing Loss: Listening to End-of-Life Transitions, an Arts-Based Approach to Midlife Mourning - Halstead, Jill; Schmid, Wolfgang (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
In this article we share our personal stories of the loss of a parent during the COVID-19-pandemic. The crisis demonstrated how the medical-scientific apparatus effectively responded to a global health emergency, but also revealed how end of life processes are professionalized in neoliberal societies, where dying and death are outsourced and sanitized, and grieving is increasingly pathologized. Drawing on our backgrounds in music and music therapy, we trace our own experiences of loss to illustrate aspects of our individual and shared bereavement process as it emerged over a 24-month period. We take an intuitive, arts-based, feminist-philosophical approach, where dying and mourning are understood as personal, social, and political events. The article is structured around the presentation of eight poetic fragments from Hearing Loss (Schmid and Halstead, 2023) a co-created digital exhibition on the theme of mourning which includes soundworks, images, narratives, short films, and poems. Through these intimate multi-modal pieces, we reflect how we do loss, and how we might speak about, and listen to, the existential, relational, and transitional experience of losing a loved one in midlife. Our work argues that practices of grieving should be encouraged, shared, and valued to ensure the mournability of every life.